The development of “problem box e-counseling” Android-based application as a medium for students’ problem disclosure - Nurul Maulida Alwi; Abdullah Pandang; Farida Aryani (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2019)
The study aimed at discovering (1) the description of the need of “problem box  e-counseling” Android-based application as a medium for students’ problem disclosure, (2) the prototype of “problem box e-counseling” Android-based application as a medium for students’ problem disclosure, and (3) the acceptance of “problem box e-counseling” Android-based application as a medium for students’ problem disclosure. This study is a development, The data were collected by interview and questionnaire techniques. This study revealed that (1) there is a high need of “problem box e-counseling” Android-based application as a medium for students’ problem disclosure at SMA Islam Athirah I Makassar (2) the prototype of “problem box e-counseling” Android-based application as a medium for students’ problem disclosure at Athirah I Islamic High School Makassar (3) the acceptance of each subject of research expert test, namely the counseling media expert, technology expert in education, and counseling practitioner in the initial product test showing positive response. Thus, the application can be accepted, and based on a test involving 10 students and a school counselor in the small group test; it indicates a very positive response (high), so it can be accepted.